Distillation of Sound Dub and the Creation of Culture. - Abbey, Eric (Intellect Books Ltd, 2022)
Distillation of Sound traces the beginnings of dub music in Jamaica and how the culture is distilled throughout the world. It focuses on the analysis of some of the most famous full-length albums of dub music and how the engineers, producers, and musicians created a new sound that changed the way that people heard music. 15 b/w illus.